Comparison of mRNA expression from Y‐chromosome X‐degenerate region genes in taurine cattle, yaks and interspecific hybrid bulls. (2nd September 2019) - Wu, Y.; Zhang, W.‐X.; Zuo, F.; Zhang, G.‐W.
Summary: The yattle (dzo) is an interspecific hybrid of the taurine cattle ( Bos taurus ) and the domestic yak ( Bos grunniens ). F1 hybrid yattle bulls are sterile due to spermatogenic arrest and have misregulation of spermatogenesis genes in the testes. However, the expression pattern of Y chromosome‐linked genes in cattle, yaks and yattle testes is still unknown. In this study, we analyzed the mRNA expression pattern of 10 genes known to be present as single copies in the X‐degenerate region of the bovine male‐specific region of the Y chromosome. Using male‐specific primers and reverse transcription quantitative PCR, the ubiquitously transcribed tetratricopeptide repeat gene, Y‐linked ( UTY ), oral‐facial‐digital syndrome 1, Y‐linked ( OFD1Y ) and ubiquitin specific peptidase 9, Y‐linked ( USP9Y ) genes were ubiquitously expressed and significantly more highly expressed in yattle than in cattle and yaks testes ( P < 0.001). RNA binding motif protein, Y‐linked ( RBMY ) had testes‐specific expression, and eukaryotic translation initiation factor 1A, Y‐linked ( EIF1AY ) was expressed mainly in testis, whereas yattle and cattle did not show significant differences with respect to the expression of RBMY and EIF1AY . Thus, based on the model of yattle bull sterility, the high expression of UTY, OFD1Y and USP9Y may be associated with yattle infertility.